1993
DOI: 10.1111/j.1476-5381.1993.tb13570.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐affinity uptake of noradrenaline in postsynaptic neurones

Abstract: 1 Neurotransmitters released from nerve endings are inactivated by re-uptake into the presynaptic nerve terminals and possibly into neighbouring glial cells. While analysing the functional properties of a,-adrenoceptors in the hypothalamus, we observed a high-affinity uptake process for noradrenaline in postsynaptic peptidergic neurones.2 In primary hypothalamic cell cultures and in a hypothalamic neuronal cell line, [3H]-prazosin bound with high affinity and was displaced by unlabelled prazosin in concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 52 publications
5
30
1
Order By: Relevance
“…Our results were not consistent with the findings of Al-Damluji et al [15]. The reason for this discrepancy is not known, but Al-Damluji et al [15] …”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Our results were not consistent with the findings of Al-Damluji et al [15]. The reason for this discrepancy is not known, but Al-Damluji et al [15] …”
Section: Discussioncontrasting
confidence: 57%
“…Moreover, we demonstrated that NA increased [Ca2+]i and depolarized membrane potentials via f3-adrenergic receptors in GT1-7 cells. Al-Damluji et al [15] found that the a1-adrenoceptor ligand [3HFprazosin bound with high affinity and was displaced by unlabelled prazosin in GT1-1 cells. Our results were not consistent with the findings of Al-Damluji et al [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AC-induced cAMP production occurs in response to dopamine and norepinephrine (Jarry et al, 1990;Martínez de la Escalera 1992b,c;Al-Damluji et al, 1993). In general, cAMP can act indirectly, by modulating various ionic currents in a protein kinase A-dependent manner, or directly, via modulation of cyclic nucleotide-gated (CNG) channels, which have been identified in GT1 neurons (Vitalis et al, 2000).…”
Section: Abstract: Gt1 Neurons; Mathematical Modeling; Voltagegated mentioning
confidence: 99%
“…While studying the functional properties of a1-adrenoceptors in the hypothalamus, we observed a high-affinity uptake process for amines in peptidergic neurones (Al-Damluji & Krsmanovic, 1992;Al-Damluji et al, 1993). In primary hypothalamic cell cultures and in a hypothalamic neuronal cell line, [3H]-prazosin bound with high affinity and was displaced by unlabelled prazosin in concentrations of 10-10 to 10-7 M. However, at concentrations of unlabelled prazosin greater than 10-7 M, there was a paradoxical increase in apparent [3H]-prazosin binding, which could be abolished by desipramine; in the presence of desipramine, unlabelled prazosin displaced [3H]-prazosin as before, but no increase in accumulation was seen above 10-7 M. The paradoxical increase of [3H]-prazosin binding was not observed in membrane preparations of hypothalamic neurones.…”
Section: Introductionmentioning
confidence: 96%